Application of in-line rheological measurements for characterization of polypropylene/opoka rock powder composites - Kloziński, Arkadiusz; Jakubowska, Paulina; Przybylska, Joanna E.; Przekop, Robert (Polimery, 2021)
The rheological properties of the composites of polypropylene (PP) with a new natural powder hybrid filler – carbonate-silicate rock called opoka – were investigated. Opoka rock is industrial waste originating (as a subsieve fraction) from the production of sorbents used in water treatment processes. The effect of opoka addition (1, 5 and 10 wt %) on the processability of PP was determined during the extrusion process using an in-line measuring stand. The testing instrument was an extruder rheometer equipped with a rheological measuring head with exchangeable dies. Cylindrical measuring dies with a radius of 1.5 mm and a length of L = 20, 30, 40 and 50 mm, respectively, were used in the measurements. The rheological parameters of the composites were determined based on the Ostwald-de-Waele power--law model at a temperature of 230 °C. The effect of the addition of opoka on the extruder operating characteristic, flow curves, viscosity curves, and the values of power law index (n), consistency factor (K), mass flow rate (MFR) and volume flow rate (MVR) have been determined.